Putative DNA G-quadruplex formation within the promoters of Plasmodium falciparum var genes - Smargiasso, Nicolas (BioMed Central, 2009)
BACKGROUND: Guanine-rich nucleic acid sequences are capable of folding into an intramolecular four-stranded structure called a G-quadruplex. When found in gene promoter regions, G-quadruplexes can downregulate gene expression, possibly by blocking the transcriptional machinery. Here we have used a genome-wide bioinformatic approach to identify Putative G-Quadruplex Sequences (PQS) in the Plasmodium falciparum genome, along with biophysical techniques to examine the physiological stability of P. falciparum PQS in vitro. RESULTS: We identified 63 PQS in the non-telomeric regions of the P. falciparum clone 3D7. Interestingly, 16 of these PQS occurred in the upstream region of a subset of the P. falciparum var genes (group B var genes). The var gene family encodes PfEMP1, the parasite's major variant antigen and adhesin expressed at the surface of infected erythrocytes, that plays a key role in malaria pathogenesis and immune evasion. The ability of the PQS found in the upstream regions of group B var genes (UpsB-Q) to form stable G-quadruplex structures in vitro was confirmed using (1)H NMR, circular dichroism, UV spectroscopy, and thermal denaturation experiments. Moreover, the synthetic compound BOQ1 that shows a higher affinity for DNA forming quadruplex rather than duplex structures was found to bind with high affinity to the UpsB-Q. CONCLUSION: This is the first demonstration of non-telomeric PQS in the genome of P. falciparum that form stable G-quadruplexes under physiological conditions in vitro. These results allow the generation of a novel hypothesis that the G-quadruplex sequences in the upstream regions of var genes have the potential to play a role in the transcriptional control of this major virulence-associated multi-gene family.